2001
DOI: 10.1128/mmbr.65.3.353-370.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ion Cycle in Bacterial Pathogens: Evidence from Cross-Genome Comparisons

Abstract: Analysis of the bacterial genome sequences shows that many human and animal pathogens encode primary membrane Na+ pumps, Na+-transporting dicarboxylate decarboxylases or Na+-translocating NADH:ubiquinone oxidoreductase, and a number of Na+-dependent permeases. This indicates that these bacteria can utilize Na+ as a coupling ion instead of or in addition to the H+ cycle. This capability to use a Na+ cycle might be an important virulence factor for such pathogens as Vibrio cholerae, Neisseria meningitidis, Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(175 citation statements)
references
References 223 publications
6
169
0
Order By: Relevance
“…It is possible that preferential amplification of the DNA template from low G + C content occurred due to the easier dissociation into single DNA strand than higher G + C templates, resulting in a bias in the favor of the former group (Suzuki and Giovannoni 1996). On the other hand, it could also be that low G + C bacteria, like acetogenic clostridia, out-number SRB at hypersaline alkaline conditions, since it is known that the acetogenic haloalkaliphiles benefit from sodium-based energetics (Häse et al 2001). This was also observed by DGGE analysis and microscopic analysis of the highest positive tubes of the serial dilutions in SRB media, which revealed the predominance of Clostridia even at the highest dilutions.…”
Section: Microbial Diversity Along a Salinity Gradientmentioning
confidence: 87%
“…It is possible that preferential amplification of the DNA template from low G + C content occurred due to the easier dissociation into single DNA strand than higher G + C templates, resulting in a bias in the favor of the former group (Suzuki and Giovannoni 1996). On the other hand, it could also be that low G + C bacteria, like acetogenic clostridia, out-number SRB at hypersaline alkaline conditions, since it is known that the acetogenic haloalkaliphiles benefit from sodium-based energetics (Häse et al 2001). This was also observed by DGGE analysis and microscopic analysis of the highest positive tubes of the serial dilutions in SRB media, which revealed the predominance of Clostridia even at the highest dilutions.…”
Section: Microbial Diversity Along a Salinity Gradientmentioning
confidence: 87%
“…Furthermore, the genes for a membrane-bound electron transport chain could be identified in the genomes of C. tetani and C. perfringens. This system shows strong similarity to the Rhodobacter-specific nitrogen fixation system of Rhodobacter capsulatus as well as to the system NADH:ubiquinone oxidoreductase found in many aerobic pathogens such as V. cholerae, Salmonella typhimurium, Y. pestis, and Haemophilus influenzae, in which it apparently functions as a Na ϩ -translocating NADH dehydrogenase (32,36). Because there are no reports for quinones in clostridia, such a NADH dehydrogenase could be involved in the fermentation of amino acids by C. tetani, as indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, at present, it is not possible to make any conclusive predictions with regard to this protein's expression level. Still, as NADHubiquinone oxidoreductase has been suggested to be indicative of bacterial virulence (Häse et al, 2001) and as the exploitation of Na þ gradients in energy metabolism has been suggested to be a widespread strategy among human pathogens, including C. pneumoniae and C. trachomatis (Häse et al, 2001), the potentially very high expression of this enzyme in P. acanthamoebae warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%